UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETIL ASETAT DAUN RAMBUSA DAN DAUN KARAMUNTING TERHADAP Streptococcus mutans - Muhammad Priyadi; Nurul Chusna; Guntur Satrio Pratomo (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2022)
Empirically, many natural ingredients have been used in preventive care for the treatment of dental and oral disorders. Chronic conditions on the teeth with the appearance of plaque and tooth decay are referred to as dental caries which are characterized by toothache and also digestive disorders. Streptococcus mutans is known as the bacteria that most often causes dental caries. Karamunting and rambusa plants have enough potential as antibacterials because there have been many studies that have shown their potential as antibacterial activities. The purpose of this study was to determine the antibacterial activity of ethyl acetate extract of karamunting leaves and rambusa leaves against Streptococcus mutans. Antibacterial activity test using well diffusion method by measuring the diameter of the inhibition zone. The results showed that the ethyl acetate extract of karamunting leaves 1%, 5%, 10%, 15%, 20% had inhibition zone diameters of 4.6 mm, 4.1 mm, 0 mm, 0 mm, 0 mm, respectively while rambusa leaves 1%, 5%, 10%, 15%, 20% had inhibition zone diameters of 4.4 mm, 8.7mm, 9.4 mm, 5.3mm and 8.8mm respectively. The ethyl acetate extract of karamunting and rambusa leaves is known to have weak antibacterial activity in the resistant category.